Electron cyclotron resonance ion source plasma characterization by energy dispersive x-ray imaging. (4th July 2017) - Rácz, R; Mascali, D; Biri, S; Caliri, C; Castro, G; Galatà, A; Gammino, S; Neri, L; Pálinkás, J; Romano, F P; Torrisi, G
Abstract: Pinhole and CCD based quasi-optical x-ray imaging technique was applied to investigate the plasma of an electron cyclotron resonance ion source (ECRIS). Spectrally integrated and energy resolved images were taken from an axial perspective. The comparison of integrated images taken of argon plasma highlights the structural changes affected by some ECRIS setting parameters, like strength of the axial magnetic confinement, RF frequency and microwave power. Photon counting analysis gives precise intensity distribution of the x-ray emitted by the argon plasma and by the plasma chamber walls. This advanced technique points out that the spatial positions of the electron losses are strongly determined by the kinetic energy of the electrons themselves to be lost and also shows evidences how strongly the plasma distribution is affected by slight changes in the RF frequency.